Prognostic value of histological subtype in intraductal papillary mucinous neoplasm of the pancreas: A retrospective analysis of outcome from one single center. Issue 15 (April 2017) - Rong, Yefei; Wang, Dansong; Xu, Chen; Ji, Yuan; Jin, Dayong; Wu, Wenchuan; Xu, Xuefeng; Kuang, Tiantao; Lou, Wenhui
Abstract : Abstract: We sought to retrospectively analyze the outcomes of patients with intraductal papillary mucinous neoplasm (IPMN) at our pancreatic surgery center, and to evaluate the prognostic value of histological subtype. The clinical data of 121 IPMNs treated in our center between 2005 and 2014 were retrospectively analyzed. Pathological slides were thoroughly reviewed by 2 specialized pathologists. Of the 121 patients, 48, 57, and 16 had main-duct, branch-duct, and mixed type IPMNs, respectively. Forty-one patients had invasive IPMNs. Histological subtypes consisted of 35 intestinal (28.9%), 56 gastric (46.3%), 29 pancreatobiliary (24.0%), and 1 oncocytic type (0.8%). Histological subtype was associated with radiological type, T stage, and degree of dysplasia ( P < .05). No significant difference in overall survival was observed among the 4 histological subtypes, regardless of whether we considered all IPMNs ( P = .106), or invasive IPMNs only ( P = .828). However, the overall survival was associated with radiological type, T stage, degree of dysplasia, lymph-node status, and nerve invasion. For invasive IPMNs, the overall survival was associated with nerve invasion and lymph-node status; however, the association between nerve invasion and overall survival lost statistical significance after multivariate analysis. Histological subtype had limited prognostic value in patients with IPMNs, and the main prognostic factor for patients with invasive IPMNs was the lymph-node status.